Pengaruh Strategi Pemasaran Terhadap Kinerja Pemasaran Minyak Kayu Putih di CV. Ruci Gemilang - Yogananta, Refo; Widayanti, Sri; Wijayati, Prasmita Dian (JURNAL AGROPLASMA, 2023)
This study aims to describe the components of the 7P marketing strategy on CV. Dewa Ruci Gemilang, analyzed the influence of the 7P marketing strategy on marketing performance, and explained the results of the research for company development. The stages of analysis using SEM-PLS go through five processes, namely the conceptualization model, determining the algorithm analysis, determining the resampling method, drawing path diagrams, and evaluating the model. The research results show that the product has a positive influence on marketing performance. Price has a positive influence on marketing performance. Place has a positive influence on marketing performance. Promotion has a positive influence on marketing performance. People have a positive influence on marketing performance. The process has a positive influence on marketing performance. Physical form has a positive influence on marketing performance.Â Keywords: Marketing strategy, marketing performance, eucalyptus oil